ANALISIS BIBLIOMETRIK DENGAN VOSVIEWER: PERKEMBANGAN PENELITIAN MANAJEMEN KINERJA PEGAWAI - Aran, Titus (Journal for Management Student (JFMS), 2024)
This study aims to  analyze the  research trends in  employee performance management using bibliometric analysis with VOSviewer, utilizing data from Google Scholar via Publish or Perish within the 2015 to 2024 timeframe. A total of 500 filtered publications were analyzed to identify publication patterns, author collaborations, and the most frequently researched topics. The analysis results revealed several main clusters dominating the literature, such as performance measurement, competency development, and human resource management. These findings indicate an increase in collaboration among authors and institutions, reflecting a collective effort to advance knowledge in the field of employee performance management. By mapping keyword and author relationships, this analysis provides a comprehensive overview of research developments during the specified period. In conclusion, this study not only confirms the relevance and importance of employee performance management in the context of modern organizations but also opens opportunities for further research that can enrich insights and practices in this field. The study's results significantly contribute to understanding the academic landscape of employee performance management and provide direction for future research.